Tahart / Takdempt: archéologie - Laporte, Jean-Pierre (Encyclopédie berbère, 2025)
Keywords: Archéologie -- Tahert

Tahart - Aillet, Cyrille (Encyclopédie berbère, 2025)
Keywords: Tahert -- Histoire

Qalhāt - Bhacker, Mohammed Reda; Bhacker, Bernadette (Encyclopaedia of Islam Three Online, 2024)
Keywords: Oman -- Histoire

The Kanem and Borno Sultanates (11th–19th Centuries) - Dewière, Rémi (Oxford Research Encyclopedia of African History, 2024)
"The Kanem and Borno Sultanates (11th–19th Centuries)" published on by Oxford University Press.
Keywords: Tchad -- Histoire

Barghash : sultan of Zanzibar (Encyclopaedia Britannica, 2024)
Barghash was the sultan of Zanzibar (1870–88), a shrewd and ambitious ruler, who, for most of his reign, looked to Britain for protection and assistance but eventually saw his domains divided between Germany and his former protector. Although not the first heir to the throne of his father, Saʿīd
Keywords: Biographies -- Zanzibar

Nāfiʿ b. al-Azraq - Gaiser, Adam R. (Encyclopaedia of Islam, 2023)
Keywords: Biographies

al-Nukkār - Gaiser, Adam R. (Encyclopaedia of Islam, 2023)
Keywords: Nukkarisme

Kitmān - Gaiser, Adam R. (Encyclopaedia of Islam, 2021)

Mukhtār b. ʿAwf al-Azdī, Abū Ḥamza - Gaiser, Adam R. (Encyclopaedia of Islam, 2022)
Keywords: Biographies

al-Mazātī - Love Jr, Paul M. (Encyclopaedia of Islam, 2022)
Keywords: Biographies

Ibadis - Gaiser, Adam R. (Routledge Handbook of Islamic Ritual and Practice, 2022)

Dragut Raïs dit Durgûth Raïs (début (XVIe siècle - 1565) - Brogini, Anne (Dictionnaire des corsaires et des pirates, 2021)
Keywords: Biographies -- Turquie

Khaïr ed-Dîn (Kheïr-ed-Din ou Khayr al-Dîn) dit Barberousse (1475?-1546) - Brogini, Anne; Buti, Gilbert (Dictionnaire des corsaires et des pirates, 2021)
Keywords: Biographies -- Turquie

Doria, famille (XVe s.-XVIe s.) - Carpentier, Bastien; Priotti, Gilbert (Dictionnaire des corsaires et des pirates, 2021)
Keywords: Biographies -- Espagne

Ibāḍiyya - Gaiser, Adam R. (Encyclopaedia of Islam, 2021)

Celsinus, M. - Vollkommer, Rainer (Allgemeines Künstlerlexikon, 2021)
Keywords: Biographies -- Djerba

Mirdās b. Udayya - Gaiser, Adam R. (Encyclopaedia of Islam, 2020)
Keywords: Biographies

Khārijīs - Gaiser, Adam R. (Encyclopaedia of Islam, 2020)
Keywords: Kharijisme

Ibn Dhakwān, Sālim - Gaiser, Adam R. (Encyclopaedia of Islam, 2020)
Keywords: Biographies -- Oman

Lawātī, Abū Muḥammad ʿAbdallāh al- - Gaiser, Adam R. (Encyclopaedia of Islam, 2020)
Keywords: Biographies

Azd al- - Webb, Peter (Encyclopaedia of Islam, 2020)

Libya until 1500 - Garnier, Sébastien (Encyclopaedia of Islam, 2020)

Djerba - Love Jr, Paul M. (Encyclopaedia of Islam, 2020)

Bārūnī, Sulaymān al- - Baldinetti, Anna (Encyclopaedia of Islam, 2021)
Keywords: Biographies -- Djebel Nefousa -- 20e siècle

Afḍalī, Yaḥyā b. Ṣāliḥ al- - Ourghi, Abdel-Hakim (Encyclopaedia of Islam, 2020)
Keywords: Biographies -- Mzab -- 19e siècle